2016
DOI: 10.20431/2349-0365.0405004
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of HIV and Plasmodium falciparum Genetic Diversity on Anaemia in HIV-patients Attending Care and Treatment Centre at Baptist Hospital Mutengene

Abstract: The aim of this study was to assess the impact of Human Immunodeficiency Virus (HIV) and KI (65.22%), MAD20 (27.54%) and RO33 (27.54%)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Although no study has been conducted to assess the diversity of P. falciparum among pregnant women with and without HIV as 2 distinct entities, a couple of studies have evaluated the diversity of P. falciparum among individuals with HIV. In Mutengene, Cameroon, it was reported that the MSP1 allelic variants detected among patients with HIV were KI (65.22%), MAD20 (27.54%), and RO33 (27.54%), while the MSP2 allelic variants were FC27 (30.43%) and 3D7/IC (31.88%), which was high and associated with anemia [ 51 ]. A study in Senegal reported no difference in genetic diversity between P. falciparum isolates from patients with malaria and concurrent malaria-arbovirus in Kedougou [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although no study has been conducted to assess the diversity of P. falciparum among pregnant women with and without HIV as 2 distinct entities, a couple of studies have evaluated the diversity of P. falciparum among individuals with HIV. In Mutengene, Cameroon, it was reported that the MSP1 allelic variants detected among patients with HIV were KI (65.22%), MAD20 (27.54%), and RO33 (27.54%), while the MSP2 allelic variants were FC27 (30.43%) and 3D7/IC (31.88%), which was high and associated with anemia [ 51 ]. A study in Senegal reported no difference in genetic diversity between P. falciparum isolates from patients with malaria and concurrent malaria-arbovirus in Kedougou [ 52 ].…”
Section: Discussionmentioning
confidence: 99%